Oncolytic viruses: a promising therapy for malignant pleural effusion and solid tumors - Wang, Xinya; Zhou, Qin; Zhang, Xuyan; Hu, Han; Liu, Binlei; Wang, Yang (Frontiers in Immunology, 2025)
Oncolytic viruses (OVs) are natural or recombinant viruses that can directly lyse tumor cells without damaging normal cells. They enhance anti-tumor immunity by releasing antigens and activating inflammatory responses within the tumor microenvironment (TME). This offers a new therapeutic approach for MPE and solid tumors. This review discusses the progress of OVs administered via intrapleural and intratumoral routes, emphasizing their potential in MPE treatment and the challenges posed by the complex intrapleural environment, which affects the direct interaction between OVs, tumor cells, and immune cells. This review also discusses the regulatory barriers, safety concerns and accessibility of oncolytic virus therapy.